Preventing a digital pearl harbour: Panetta's key recommendations - Heinl, Caitriona H. (2013)
Many states are grappling with the burning question fo how best to defend a nation from cyber attack. US Secretary of Defence Leon Panetta recently outlined key best preactices in the United States for what last is a universal problem.